Synthesis, structure characterization, Hirshfeld surface analysis, and computational studies of 3-nitro-1,2,4-triazol-5-one (NTO):acridine - Sen, Nilgun; Pons, Jean-Francois; Zorlu, Yunus; Dossi, Eleftheria; Persico, Federica; Temple, Tracey; Aslan, Nazife (Springer/Plenum Publishers, 2024)
To modify the physical features and extend applications of the 3-nitro-1,2,4-triazol-5-one (NTO), we synthesized NTO with acridine (ACR) at a molar ratio of 1:1, a neutralization reaction. Through altering the chemical composition, it was possible to alter physical properties such as thermal stability, free space (voids), packing coefficient, crystal density, difference in pKa of co-formers, morphology, solubility, and impact sensitivity, and detonation parameters . It appears that physical attributes could be entirely altered. Single-crystal and powder X-ray diffraction methods, infrared spectroscopy, mass spectrometry, nuclear magnetic resonance spectroscopy (1H-NMR and 13C-NMR), and thermal analysis were utilized to comprehensively characterize and confirm the formation of the structure of NTO:ACR. The substantial hydrogen bond interactions and planar layered structures observed between the cations and anions generated a complex 3D network, providing insight into the structure-property interrelationship. One intriguing feature discovered is the layered structure present in NTO:ACR, which may be responsible for the low impact sensitivity. According to the experimental results, NTO:ACR showed good thermal stability (Td = 229 degrees C) and outstanding impact sensitivity (IS = 100 J). Detonation velocity and pressure were calculated using the EXPLO5 software program and found to be 7006 ms-1 and 20.02 GPa, respectively.
Keywords: Energetic salts; 3-Nitro-1,2,4-triazol-5-one; Acridine; Non-covalent interactions; NTO